2021
DOI: 10.3171/2020.1.jns19788
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative embolization versus no embolization for WHO grade I intracranial meningioma: a retrospective matched cohort study

Abstract: OBJECTIVEThe controversy continues over the clinical utility of preoperative embolization for reducing tumor vascularity of intracranial meningiomas prior to resection. Previous studies comparing embolization and nonembolization patients have not controlled for detailed tumor parameters before assessing outcomes.METHODSThe authors reviewed the cases of all patients who underwent resection of a WHO grade I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 24 publications
3
13
1
Order By: Relevance
“…Our data showed that preoperative embolization could significantly reduce the rate of surgical complication and the possibilities of mRS decline, which were distinct from others (7,12). Sensory and motor function deficits were the majority of postsurgical complications and contribute to degrees of daily life disabilities, as shown in Tables 3 and 4.…”
Section: Discussionmentioning
confidence: 48%
See 4 more Smart Citations
“…Our data showed that preoperative embolization could significantly reduce the rate of surgical complication and the possibilities of mRS decline, which were distinct from others (7,12). Sensory and motor function deficits were the majority of postsurgical complications and contribute to degrees of daily life disabilities, as shown in Tables 3 and 4.…”
Section: Discussionmentioning
confidence: 48%
“…Specifically, the maximum tumor diameter, which differs significantly between groups in the original unmatched dataset (p < 0.0001), reached a statistical intergroup balance after matching (p = 0.69). Such bias also exists in other studies (7,12), which may indicate surgeons' preferences to embolize potential risky meningiomas. The rationales of preoperative embolization include the reduction of intraoperative blood loss and softening of the tumor mass to ease surgical operation and reduce surgery duration.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations